A preparation method of TC19 titanium alloy

By doping rare earth and silicon carbide particles in TC19 titanium alloy, and using discharge plasma sintering and hydrogen-free carbon-nitrogen co-permeability processes, the problems of poor wear resistance and low corrosion resistance of TC19 titanium alloy are solved, significantly improving its mechanical properties and service life.

CN119177415BActive Publication Date: 2025-03-14昱华先进材料科技(陕西)有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411677927.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-14
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

In practical applications, TC19 titanium alloy has problems such as poor wear resistance, low corrosion resistance and short service life, and the existing smelting process is difficult to ensure the uniformity of components and the excellent solidification structure.

Method used

Rare earth doped titanium alloy by doping rare earth and silicon carbide particles in TC19 titanium alloy and using discharge plasma sintering process, followed by surface treatment of hydrogen-free carbon-nitrogen co-penetration process to form a highly hard and wear-resistant modified layer.

Benefits of technology

It significantly improves the wear, corrosion and tensile resistance of TC19 titanium alloy, extends the service life, and optimizes the structure and mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of titanium alloys and discloses a preparation method of TC19 titanium alloy. After being refined, silicon carbide particles can generate grain boundaries with high volume density, hindering the movement of dislocations and the extension of dislocations to adjacent grains. Rare earth has the function of purifying alloy liquid and effectively refining the structure. Boron element can generate boron carbide in situ with titanium element in the titanium alloy. During the stretching process of the titanium alloy, the load can be transferred from the matrix to the boron carbide particles, so that the matrix bears the energy of the load, and the resistance to the movement of dislocations is increased, thereby improving the strength and hardness of the titanium alloy material. After the TC19 titanium alloy is carbonitrided, titanium carbide and titanium nitride ceramic wear-resistant phases can be generated on the surface of the titanium alloy. At the same time, carbon and nitrogen can be dissolved in the titanium matrix, which has the function of solid solution strengthening, improves the wear resistance and corrosion resistance, and enhances its mechanical properties, thereby broadening the further application of the TC19 titanium alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of titanium alloys, and in particular to a method for preparing a TC19 titanium alloy. Background Art

[0002] Titanium alloys have the remarkable characteristics of high specific strength, good corrosion resistance, and high temperature resistance. They are widely used in aerospace, chemical, medical and other fields. At the same time, more and more key rotating parts such as integral blades of aircraft engine compressors are made of titanium alloys to achieve the purpose of weight reduction; among them, TC19 titanium alloy is a more typical grade of this type of titanium alloy. The nominal composition of TC19 titanium alloy is Ti-6Al-2Sn-4Zr-6Mo (mass percentage), which belongs to the martensitic α+β type heat-resistant titanium alloy. The physical and mechanical properties of this alloy are also very excellent. However, titanium alloys have low plastic shear resistance and work hardening properties, which are not enough to resist friction and wear caused by mechanical properties (such as adhesion, abrasive wear, etc.). TC19 titanium alloy has poor wear resistance and low corrosion resistance, which greatly limits its wider application. Therefore, the preparation of a TC19 titanium alloy has become a hot topic in current research.

[0003] TC19 titanium alloy is widely used in aviation equipment, biopharmaceuticals, ships and warships, petrochemicals and other fields due to its high biocompatibility, low corrosion level, excellent mechanical strength and toughness. However, due to its defects such as low surface hardness, poor wear resistance and low service life, it cannot meet the needs well in actual application. The most commonly used smelting method for TC19 titanium alloy is vacuum consumable arc furnace smelting, but since the electrode melts and solidifies at the same time during vacuum consumable arc melting, the molten pool is relatively small and cannot fully diffuse the alloy elements to improve the uniformity of composition. For TC19, an engine material with a high degree of alloying and a particularly large difference in the melting points of alloy elements, the current smelting process is difficult to achieve a level where the solidification structure and composition uniformity do not decrease.

[0004] Both chemical vapor deposition and physical vapor deposition can deposit a film of a certain thickness on the surface of the titanium alloy substrate, which can improve the hardness and wear resistance of the titanium alloy surface layer. However, conventional chemical vapor deposition has high requirements on temperature, the deposition rate is not large, and this method is difficult to deposit a film on a local or certain surface of the substrate; although physical vapor deposition has little thermal effect on the substrate material, the resulting coating has poor density, weak bonding with the substrate, and the coating is easy to fall off, which cannot meet the needs of the actual production process; laser processing uses an electron beam to fuse the prefabricated cladding layer and the titanium alloy substrate material together to form a composite coating with high strength and high hardness, but this technology is prone to uneven tissue distribution and uneven stress distribution, and is expensive.

[0005] In the prior art, carburizing is a simple and effective method; however, hydrogen always penetrates into the matrix during carburizing, resulting in hydrogen embrittlement, which seriously affects the carburizing quality of titanium materials, directly manifested in that the plasticity, toughness and tensile strength of the material are greatly reduced, and cracks and peeling are easily formed on the surface of the titanium alloy; therefore, the present invention aims to add rare earth boron elements, smelt with TC19 titanium alloy, and synthesize boron carbide wear-resistant particles in situ; at the same time, the rare earth elements have the effect of purifying the alloy liquid, and obtain TC19 titanium alloy through the surface hydrogen-free carbonitriding process, thereby significantly improving the wear resistance, corrosion resistance and tensile resistance of the titanium alloy. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing TC19 titanium alloy. By doping and surface modifying the TC19 titanium alloy, a modified layer with corrosion resistance, wear resistance and good stability is prepared, which can effectively expand its scope of use and extend its service life.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A method for preparing TC19 titanium alloy comprises the following steps:

[0009] Step (1), washing the rare earth doped titanium alloy with 20-40% by mass citric acid, polishing it with 600-1000 sandpaper, cleaning it in an ultrasonic processor for 5-15 minutes, then cleaning and degreasing it with acetone, cleaning it with alcohol and drying it to obtain a surface treated titanium alloy.

[0010] Step (2), plasma carbonitriding experiment is carried out using a double glow ion metal diffusion furnace. The surface treated titanium alloy and the insulation cover are placed on the cathode workbench in the vacuum chamber. The graphite is placed on the source ring and covered with a steel cover. The distance between the center of the graphite source and the cathode workbench is adjusted and kept on the same vertical line. The vacuum is evacuated to 3×10 -2 -6×10 -2 Pa, set the gas pressure of argon and nitrogen to 25-45Pa, adjust the cathode voltage, perform discharge bombardment activation on the surface of the titanium alloy for 2-5min, adjust the source voltage, heat and perform plasma carbonitriding treatment. After the treatment, the thickness of the diffusion layer is 50-250μm. Turn off the furnace, take samples, and cool to room temperature to obtain TC19 titanium alloy.

[0011] Furthermore, the power of the ultrasonic processor in step (1) is 500-800W.

[0012] Furthermore, in step (2), the cathode voltage is 300-450V and the source voltage is 600-850V.

[0013] Furthermore, in step (2), the distance between the center of the graphite source stage and the cathode workbench is 10-20 cm.

[0014] Furthermore, in step (2), the plasma carbonitriding treatment temperature is 700-900° C., and the treatment time is 1-3 h.

[0015] Furthermore, the method for preparing the rare earth-doped titanium alloy in step (1) comprises the following steps:

[0016] Step S1, placing TC19 titanium alloy, silicon carbide particles and rare earth boride in a planetary ball mill, using GCr15 steel balls with a diameter of 2-4 mm for ball milling, the ball-to-material mass ratio is (3-5):1, the ball mill speed is 300-500 r / min, the ball milling time is 4-8 h, and a rare earth-doped titanium alloy mixed powder is obtained.

[0017] Step S2, placing the rare earth doped titanium alloy mixed powder in a graphite mold, cold isostatic pressing at 200-300MPa, sintering in a spark plasma sintering furnace, adjusting the heating rate and vacuum degree, first keeping warm at 1050-1200°C for 1-3h, then keeping warm at 850-950°C for 20-40min, and finally keeping warm at 600-700°C for 2-4h, air cooling to room temperature, to obtain a rare earth doped titanium alloy.

[0018] Furthermore, in step S1, the rare earth boride is any one of lanthanum hexaboride, cerium hexaboride or yttrium hexaboride.

[0019] Furthermore, in step S1, by weight, the TC19 titanium alloy is 100 parts, the silicon carbide particles are 0.1-0.5 parts, and the rare earth boride is 0.3-1.5 parts.

[0020] Furthermore, in step S2, the heating rate is 80-100°C / min, and the vacuum degree is 2×10 -3 -5×10 -3 Pa.

[0021] By adopting the above technical solution, the beneficial effects of the present invention are:

[0022] The present invention adopts a planetary ball mill to ball-mill TC19 titanium alloy powder, silicon carbide particles and rare earth boride, utilizes a discharge plasma sintering process to prepare a rare earth-doped titanium alloy, then grinds and cleans the rare earth-doped titanium alloy, adopts a hydrogen-free carbonitriding process to perform surface treatment on the alloy, and obtains the TC19 titanium alloy by optimizing the process parameters.

[0023] After refinement, silicon carbide particles can produce high volume density grain boundaries, hindering the movement of dislocations and the extension of dislocations to adjacent grains, thereby strengthening the titanium alloy material; rare earth borides contain rare earth and boron elements, among which rare earth has the function of purifying the alloy liquid and effectively refining the structure, and boron element can generate boron carbide in situ with titanium element in titanium alloy. During the stretching process of titanium alloy, the load can be transferred from the matrix to the boron carbide particles, so that the matrix bears the energy of the load, increasing the resistance to dislocation movement, thereby improving the strength and hardness of the titanium alloy material.

[0024] After carbonitriding, TC19 titanium alloy can generate titanium carbide and titanium nitride ceramic wear-resistant phases on the surface of the titanium alloy. At the same time, carbon and nitrogen can be dissolved into the titanium matrix, which has the effect of solid solution strengthening, improves the wear resistance and reduces the wear rate. The hydrogen-free carbonitriding process is adopted, which can form a uniform, dense, crack-free and smooth corrosion-resistant coating on the surface of the titanium alloy, avoiding the hydrogen evolution problem caused by the ordinary carbonitriding process, thereby causing damage to the mechanical properties of the matrix material itself. A surface hardening layer of a certain thickness can be obtained in a short time, which improves the efficiency of the surface modification treatment of the titanium alloy, significantly improves the wear and corrosion resistance of the titanium alloy, and enhances its mechanical properties, broadening the further application of TC19 titanium alloy.

[0025] The use of gradient slow cooling process to prepare rare earth doped titanium alloy has the following advantages: (1) The difference in cooling rate makes the grain growth rate of different regions of titanium alloy different, which can achieve precise control of the microstructure of titanium alloy, and then form a gradient grain structure, thereby refining the grains and helping to improve the strength and toughness of titanium alloy; (2) Due to the existence of temperature gradient, the hardness of titanium alloy will also show a gradient distribution, which helps to improve the adaptability and durability of titanium alloy under different stress conditions; (3) During the gradient slow cooling process, the rare earth doping elements and the titanium alloy matrix can produce a synergistic strengthening effect, further improving the mechanical properties of titanium alloy. Therefore, the gradient temperature control process has a significant impact on the manufacturing process of titanium alloy, which can optimize the organizational structure and mechanical properties of titanium alloy materials, reduce defect formation, and improve the overall quality and performance of the material. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] (1) 100 parts by weight of TC19 titanium alloy, 0.1 parts of silicon carbide particles and 0.3 parts of lanthanum hexaboride were placed in a planetary ball mill and ball milled using a GCr15 steel ball with a diameter of 3 mm. The ball-to-material mass ratio was 4:1. The ball mill speed was 400 r / min and the ball milling time was 5 h to obtain a rare earth-doped titanium alloy mixed powder.

[0029] (2) The rare earth doped titanium alloy mixed powder was placed in a graphite mold and cold isostatically pressed at 250 MPa. The mixture was sintered in a spark plasma sintering furnace with a heating rate of 90 °C / min and a vacuum degree of 3 × 10 -3 Pa, first keep it at 1150 ° C for 2 h, then keep it at 900 ° C for 30 min, and finally keep it at 650 ° C for 3 h. Air-cool it to room temperature to obtain a rare earth doped titanium alloy.

[0030] Example 2

[0031] (1) 100 parts by weight of TC19 titanium alloy, 0.2 parts of silicon carbide particles and 0.6 parts of cerium hexaboride were placed in a planetary ball mill and ball milled using a GCr15 steel ball with a diameter of 4 mm. The ball-to-material mass ratio was 3:1. The ball mill speed was 500 r / min and the ball milling time was 4 h to obtain a rare earth-doped titanium alloy mixed powder.

[0032] (2) The rare earth doped titanium alloy mixed powder was placed in a graphite mold and cold isostatically pressed at 300 MPa. The mixture was sintered in a spark plasma sintering furnace with a heating rate of 100 °C / min and a vacuum degree of 5 × 10 -3 Pa, first keep it at 1200℃ for 1h, then keep it at 950℃ for 20min, and finally keep it at 700℃ for 2h, and air-cool it to room temperature to obtain rare earth doped titanium alloy.

[0033] Example 3

[0034] (1) 100 parts by weight of TC19 titanium alloy, 0.3 parts of silicon carbide particles and 0.9 parts of yttrium hexaboride were placed in a planetary ball mill and ball milled using a GCr15 steel ball with a diameter of 2 mm. The ball-to-material mass ratio was 5:1. The ball mill speed was 300 r / min and the ball milling time was 8 h to obtain a rare earth-doped titanium alloy mixed powder.

[0035] (2) The rare earth doped titanium alloy mixed powder was placed in a graphite mold and cold isostatically pressed at 200 MPa. The mixture was sintered in a spark plasma sintering furnace with a heating rate of 80 °C / min and a vacuum degree of 2 × 10 -3 Pa, first keep it at 1050℃ for 3h, then keep it at 850℃ for 40min, finally keep it at 600℃ for 2h, and air-cool it to room temperature to obtain rare earth doped titanium alloy.

[0036] Example 4

[0037] (1) 100 parts by weight of TC19 titanium alloy, 0.4 parts of silicon carbide particles and 1.2 parts of lanthanum hexaboride were placed in a planetary ball mill and ball milled using GCr15 steel balls with a diameter of 3.5 mm. The ball-to-material mass ratio was 4:1. The ball mill speed was 350 r / min and the ball milling time was 7 h to obtain a rare earth-doped titanium alloy mixed powder.

[0038] (2) The rare earth doped titanium alloy mixed powder was placed in a graphite mold and cold isostatically pressed at 280 MPa. The mixture was sintered in a spark plasma sintering furnace with a heating rate of 95 °C / min and a vacuum degree of 4 × 10 -3 Pa, first keep it at 1100 ° C for 2 h, then keep it at 920 ° C for 35 min, and finally keep it at 660 ° C for 3 h. Air-cool it to room temperature to obtain a rare earth doped titanium alloy.

[0039] Example 5

[0040] (1) 100 parts by weight of TC19 titanium alloy, 0.5 parts of silicon carbide particles and 1.5 parts of cerium hexaboride were placed in a planetary ball mill and ball milled using a GCr15 steel ball with a diameter of 3 mm. The ball-to-material mass ratio was 5:1. The ball mill speed was 450 r / min and the ball milling time was 5 h to obtain a rare earth-doped titanium alloy mixed powder.

[0041] (2) The rare earth doped titanium alloy mixed powder was placed in a graphite mold and cold isostatically pressed at 220 MPa. The mixture was sintered in a spark plasma sintering furnace with a heating rate of 85 °C / min and a vacuum degree of 5 × 10 -3 Pa, first keep it at 1200 ° C for 3 h, then keep it at 900 ° C for 30 min, and finally keep it at 700 ° C for 3 h, and air-cool it to room temperature to obtain a rare earth doped titanium alloy.

[0042] Comparative Example 1

[0043] (1) 100 parts by weight of TC19 titanium alloy were placed in a planetary ball mill and ball-milled using a GCr15 steel ball with a diameter of 3 mm. The ball-to-material mass ratio was 4:1. The ball mill speed was 400 r / min and the ball milling time was 5 h to obtain TC19 titanium alloy powder.

[0044] (2) TC19 titanium alloy powder was placed in a graphite mold and cold isostatically pressed at 250 MPa. The powder was sintered in a spark plasma sintering furnace with a heating rate of 90 °C / min and a vacuum degree of 3 × 10 -3Pa, first keep it at 1150 ℃ for 2h, then keep it at 900 ℃ for 30min, finally keep it at 650 ℃ for 3h, air-cool to room temperature, and obtain TC19 titanium alloy.

[0045] Tensile strength test: Referring to the standard GB / T 228-2002, an electronic universal testing machine was used to test the room temperature tensile properties of titanium alloy, with a tensile rate of 0.5 mm / min.

[0046] Vickers hardness test: Referring to the standard GB / T4340.1-1999, a digital microhardness tester is used to test the microhardness of titanium alloy. The indenter is made of diamond, the load is 4.9N, and the holding time is 15s.

[0047] Table 1 Mechanical properties test

[0048]

[0049] It can be seen from the test results in the above table that with the increase of the content of silicon carbide particles and rare earth borides, the tensile strength and hardness of the titanium alloy gradually increase, wherein the tensile strength in Example 4 is 1083MPa, and the Vickers hardness is 917.0HV, which is significantly increased compared with the comparative example 1 to which silicon carbide particles and rare earth borides are not added. This is because, on the one hand, after refinement, the silicon carbide particles can produce grain boundaries with high volume density, hindering the movement of dislocations and the extension of dislocations to adjacent grains, thereby strengthening the titanium alloy material; on the other hand, the rare earth boride contains rare earth and boron elements, wherein the rare earth has the function of purifying the alloy liquid and effectively refining the structure, and the boron element can generate boron carbide in situ with the titanium element in the titanium alloy. During the stretching process of the titanium alloy, the load can be transferred from the matrix to the boron carbide particles, so that the matrix bears the energy of the load, and increases the resistance to dislocation movement, thereby improving the strength and hardness of the titanium alloy material.

[0050] Wear resistance test: A friction and wear testing machine was used to carry out ball-disc friction test. The friction part was the prepared TC19 titanium alloy, and the friction pair was a GCr15 ball with a diameter of 5 mm and a surface hardness of 60HRC. The test conditions were dry friction, a load of 50 gf, a speed of 1300 r / min, and a time of 30 min.

[0051] Table 2 Wear resistance test

[0052]

[0053] It can be seen from the test data in the above table that with the increase of silicon carbide particles and rare earth boride content, the larger the volume fraction of refined carbides, the higher the hardness, and the better the wear resistance; this is because silicon carbide and boron carbide have good resistance to abrasive wear and can transfer loads. When titanium alloy is subjected to external friction, the friction pair will form relatively large notches or grooves on its surface. For carbide particles with a smaller content, they can be "plowed" out in one sliding pass; while for carbides with a larger content, it may take multiple passes to break them or "plow" them off, so the wear resistance of titanium alloy is enhanced.

[0054] Example 6

[0055] (1) The rare earth-doped titanium alloy (prepared in Example 4) was washed with 30% by mass citric acid, polished with 800 sandpaper, and cleaned in an ultrasonic processor with a power of 600 W for 10 min. Then, it was cleaned and degreased with acetone, cleaned and dried with alcohol, and a surface-treated titanium alloy was obtained.

[0056] (2) Plasma carbonitriding experiment was carried out in a double glow ion metal infiltration furnace. The surface treated titanium alloy and the insulation cover were placed on the cathode workbench in the vacuum chamber. The graphite was placed on the source ring and covered with a steel cover. The distance between the center of the graphite source and the cathode workbench was adjusted and kept on the same vertical line. The distance was 15 cm and the vacuum was evacuated to 4×10 -2 Pa, set the gas pressure of argon and nitrogen to 40Pa, adjust the cathode voltage to 400V, perform discharge bombardment activation on the titanium alloy surface for 3min, adjust the source voltage to 750V, and perform plasma carbonitriding treatment at 800℃ for 2h. After the treatment, the thickness of the diffusion layer is 50μm. Turn off the furnace, take samples, and cool to room temperature to obtain TC19 titanium alloy.

[0057] Example 7

[0058] (1) The rare earth-doped titanium alloy (prepared in Example 4) was washed with 40% by mass citric acid, polished with No. 600 sandpaper, and cleaned in an ultrasonic processor with a power of 800 W for 5 minutes. Then, it was cleaned and degreased with acetone, cleaned and dried with alcohol, and a surface-treated titanium alloy was obtained.

[0059] (2) Plasma carbonitriding experiment was carried out in a double glow ion metal infiltration furnace. The surface treated titanium alloy and the insulation cover were placed on the cathode workbench in the vacuum chamber. The graphite was placed on the source ring and covered with a steel cover. The distance between the center of the graphite source and the cathode workbench was adjusted and kept on the same vertical line. The distance was 20 cm and the vacuum was evacuated to 6×10 -2Pa, set the gas pressure of argon and nitrogen to 45Pa, adjust the cathode voltage to 450V, perform discharge bombardment activation on the titanium alloy surface for 2min, adjust the source voltage to 850V, and perform plasma carbonitriding treatment at 900℃ for 1h. After the treatment, the thickness of the diffusion layer is 100μm. Turn off the furnace, take samples, and cool to room temperature to obtain TC19 titanium alloy.

[0060] Example 8

[0061] (1) The rare earth-doped titanium alloy (prepared in Example 4) was washed with 20% by mass citric acid, polished with No. 1000 sandpaper, and cleaned in an ultrasonic processor with a power of 500 W for 15 min. Then, it was cleaned and degreased with acetone, cleaned and dried with alcohol, and a surface-treated titanium alloy was obtained.

[0062] (2) Plasma carbonitriding experiment was carried out in a double glow ion metal infiltration furnace. The surface treated titanium alloy and the insulation cover were placed on the cathode workbench in the vacuum chamber. The graphite was placed on the source ring and covered with a steel cover. The distance between the center of the graphite source and the cathode workbench was adjusted and kept on the same vertical line. The distance was 10 cm and the vacuum was evacuated to 3×10 -2 Pa, set the gas pressure of argon and nitrogen to 25Pa, adjust the cathode voltage to 300V, perform discharge bombardment activation on the titanium alloy surface for 5min, adjust the source voltage to 600V, and perform plasma carbonitriding at 700℃ for 3h. After the treatment, the thickness of the diffusion layer is 150μm. Turn off the furnace, take samples, and cool to room temperature to obtain TC19 titanium alloy.

[0063] Example 9

[0064] (1) The rare earth-doped titanium alloy (prepared in Example 4) was washed with 35% by mass citric acid, polished with 900 sandpaper, and cleaned in an ultrasonic processor with a power of 600 W for 12 min. It was then cleaned and degreased with acetone, cleaned and dried with alcohol to obtain a surface-treated titanium alloy.

[0065] (2) Plasma carbonitriding experiment was carried out in a double glow ion metal diffusion furnace. The surface treated titanium alloy and the insulation cover were placed on the cathode workbench in the vacuum chamber. The graphite was placed on the source ring and covered with a steel cover. The distance between the center of the graphite source and the cathode workbench was adjusted and kept on the same vertical line. The distance was 12 cm and the vacuum was evacuated to 4×10 -2 Pa, set the gas pressure of argon and nitrogen to 30Pa, adjust the cathode voltage to 350V, perform discharge bombardment activation on the titanium alloy surface for 4min, adjust the source voltage to 750V, and perform plasma carbonitriding at 850℃ for 2h. After the treatment, the thickness of the diffusion layer is 200μm. Turn off the furnace, take samples, and cool to room temperature to obtain TC19 titanium alloy.

[0066] Example 10

[0067] (1) The rare earth-doped titanium alloy (prepared in Example 4) was washed with 25% by mass citric acid, polished with No. 700 sandpaper, and cleaned in an ultrasonic processor with a power of 600 W for 10 min. It was then cleaned and degreased with acetone, cleaned and dried with alcohol to obtain a surface-treated titanium alloy.

[0068] (2) Plasma carbonitriding experiment was carried out in a double glow ion metal diffusion furnace. The surface treated titanium alloy and the insulation cover were placed on the cathode workbench in the vacuum chamber. The graphite was placed on the source ring and covered with a steel cover. The distance between the center of the graphite source and the cathode workbench was adjusted and kept on the same vertical line. The distance was 15 cm and the vacuum was evacuated to 5×10 -2 Pa, set the gas pressure of argon and nitrogen to 40Pa, adjust the cathode voltage to 400V, perform discharge bombardment activation on the titanium alloy surface for 5min, adjust the source voltage to 800V, and perform plasma carbonitriding at 850℃ for 2h. After the treatment, the thickness of the diffusion layer is 250μm. Turn off the furnace, take samples, and cool to room temperature to obtain TC19 titanium alloy.

[0069] Comparative Example 2

[0070] (1) The rare earth-doped titanium alloy (prepared in Comparative Example 1) was washed with 30% by mass citric acid, polished with 800 sandpaper, and cleaned in an ultrasonic processor with a power of 600 W for 10 min. Then, it was cleaned and degreased with acetone, cleaned and dried with alcohol, and a surface-treated titanium alloy was obtained.

[0071] (2) Plasma carbonitriding experiment was carried out in a double glow ion metal infiltration furnace. The surface treated titanium alloy and the insulation cover were placed on the cathode workbench in the vacuum chamber. The graphite was placed on the source ring and covered with a steel cover. The distance between the center of the graphite source and the cathode workbench was adjusted and kept on the same vertical line. The distance was 15 cm and the vacuum was evacuated to 4×10 -2 Pa, set the gas pressure of argon and nitrogen to 40Pa, adjust the cathode voltage to 400V, perform discharge bombardment activation on the titanium alloy surface for 3min, adjust the source voltage to 750V, and perform plasma carbonitriding treatment at 800℃ for 2h. After the treatment, the thickness of the diffusion layer is 50μm. Turn off the furnace, take samples, and cool to room temperature to obtain TC19 titanium alloy.

[0072] Comparative Example 3

[0073] The rare earth-doped titanium alloy (prepared in Example 6) was washed with 30% by mass citric acid, polished with No. 800 sandpaper, cleaned in an ultrasonic processor with a power of 600 W for 10 minutes, then cleaned and degreased with acetone, cleaned and dried with alcohol, and a surface-treated titanium alloy was obtained.

[0074] Corrosion resistance test: The prepared titanium alloy was cleaned with alcohol and dried, its initial weight was measured as m1, and it was immersed in a sulfuric acid aqueous solution with a mass fraction of 80%. After 168 hours, it was taken out and its weight was measured as m2, and the corrosion rate was calculated.

[0075] Wear resistance test: A friction and wear testing machine was used to carry out ball-disc friction test. The friction part was the prepared TC19 titanium alloy, and the friction pair was a GCr15 ball with a diameter of 5 mm and a surface hardness of 60HRC. The test conditions were dry friction, a load of 50 gf, a speed of 1300 r / min, and a time of 30 min.

[0076] Table 3 Wear resistance and corrosion resistance test

[0077]

[0078] It can be seen from the test results in the above table that with the increase in the thickness of the carbonitriding layer on the surface of the titanium alloy, the corrosion resistance and wear resistance of the titanium alloy are gradually enhanced. In Example 9, the wear rate is 0.0020 g / h and the corrosion rate is 1.852 mm / a, indicating that on the one hand, the wear rate of the titanium alloy can be reduced after carbonitriding. This is because after carbonitriding, titanium carbide and titanium nitride ceramic wear-resistant phases are generated on the surface of the titanium alloy. At the same time, carbon and nitrogen can be dissolved in the titanium matrix, which has the effect of solid solution strengthening, improves the wear resistance and reduces the wear rate; on the other hand, On the one hand, the hydrogen-free carbonitriding process is adopted, which can form a uniform, dense, crack-free and smooth corrosion-resistant coating on the surface of the titanium alloy, avoiding the hydrogen evolution problem caused by the ordinary carbonitriding process, thereby causing damage to the mechanical properties of the matrix material itself; in comparative example 2, the silicon carbide particles and rare earth borides are not modified, but its surface is treated by the hydrogen-free carbonitriding process, and its corrosion resistance is better; in comparative example 3, the silicon carbide particles and rare earth borides are modified, but its surface is not treated by the hydrogen-free carbonitriding process, and its wear resistance is not as good as that of the embodiment.

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing TC19 titanium alloy, characterized in that: The preparation method comprises the following steps: Step (1), washing the rare earth doped titanium alloy with 20-40% by mass citric acid, polishing it with 600-1000 sandpaper, cleaning it in an ultrasonic processor for 5-15 minutes, then cleaning and degreasing it with acetone, cleaning it with alcohol and drying it to obtain a surface treated titanium alloy; Step (2), a plasma carbonitriding experiment is carried out using a double glow ion metal diffusion furnace. The surface treated titanium alloy and the insulation cover are placed on the cathode workbench in the vacuum chamber. The graphite is placed on the source ring and covered with a steel cover. The distance between the center of the graphite source and the cathode workbench is adjusted and kept on the same vertical line. The vacuum is evacuated to 3×10 -2 -6×10 -2 Pa, set the gas pressure of argon and nitrogen to 25-45Pa, adjust the cathode voltage, perform discharge bombardment activation on the surface of the titanium alloy for 2-5min, adjust the source voltage, heat and perform plasma carbonitriding treatment, after the treatment, the thickness of the carbonitriding layer is 50-250μm, close the furnace and take samples, cool to room temperature, and obtain TC19 titanium alloy; The method for preparing the rare earth-doped titanium alloy in step (1) comprises the following steps: Step S1, placing TC19 titanium alloy, silicon carbide particles and rare earth boride in a planetary ball mill, using GCr15 steel balls with a diameter of 2-4 mm for ball milling, the ball-to-material mass ratio is (3-5):1, the ball mill speed is 300-500 r / min, the ball milling time is 4-8 h, and a rare earth-doped titanium alloy mixed powder is obtained; Step S2, placing the rare earth doped titanium alloy mixed powder in a graphite mold, cold isostatic pressing at 200-300 MPa, sintering in a spark plasma sintering furnace, adjusting the heating rate and vacuum degree, first keeping warm at 1050-1200° C. for 1-3 h, then keeping warm at 850-950° C. for 20-40 min, and finally keeping warm at 600-700° C. for 2-4 h, and air cooling to room temperature to obtain a rare earth doped titanium alloy; In the step S1, by weight, TC19 titanium alloy is 100 parts, silicon carbide particles are 0.1-0.5 parts, and rare earth boride is 0.3-1.5 parts.

2. The method for preparing the TC19 titanium alloy according to claim 1, characterized in that: The power of the ultrasonic processor in step (1) is 500-800W.

3. The method for preparing the TC19 titanium alloy according to claim 1, characterized in that: In the step (2), the cathode voltage is 300-450V, and the source voltage is 600-850V.

4. The method for preparing the TC19 titanium alloy according to claim 1, characterized in that: In the step (2), the distance between the center of the graphite source and the cathode workbench is 10-20 cm.

5. The method for preparing the TC19 titanium alloy according to claim 1, characterized in that: The plasma carbonitriding treatment temperature in step (2) is 700-900° C., and the treatment time is 1-3 hours.

6. The method for preparing the TC19 titanium alloy according to claim 1, characterized in that: In step S1, the rare earth boride is any one of lanthanum hexaboride, cerium hexaboride or yttrium hexaboride.

7. The method for preparing the TC19 titanium alloy according to claim 1, characterized in that: In step S2, the heating rate is 80-100°C / min, and the vacuum degree is 2×10 -3 -5×10 -3 Pa.

Citation Information

Patent Citations

  • Preparation method for catalytic plasma nitrocarburized and diamond-like carbon composite film

    CN101871086A

  • Non-hydrogen carbonizing equipment and technology by dual-glow diocharge

    CN1390976A